Genomic insights into the spread of methicillin-resistant Staphylococcus aureus involved in ear infections - Zhewei Sun; Jinhong Chen; Chunhong Liu; Yueru Tian; Fuqi Ai; Jiaying Du; Wangxiao Zhou; Wenjun Cao; Ming Guan; Baixing Ding (BMC Infectious Diseases)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen causing ear infections. However, genomic epidemiology and determinants influencing transmission of ear infections associated MRSA (EIA-MRSA) in community remain unknown. Methods In 2020–2021, 105 EIA-MRSA isolates were collected and sequenced from outpatients across different households in Shanghai, China. Antimicrobial susceptibility testing, core genome MLST, and phylodynamic analyses were conducted to characterize EIA-MRSA dissemination. Results Quinolone resistance was identified as a risk factor for EIA-MRSA spread (OR 9, [95% CI 3–31]). The ST764 clone and two subclones of ST22-PT hypervirulent clone have developed an extensive quinolone-resistant (eQR) phenotype, conferring additional resistance to advanced quinolones due to the accumulation of four mutations in gyrA (S84L and either S85P, E88K, or E88G) and parC (S80F and either E84K or E84G). These ST764- and ST22-PT-eQR isolates were highly transmissible and showed increased resistance to other commonly used antimicrobials, posing potential high-risk clones. The eQR phenotype may be inherent to the ST764 lineage, which emerged in the late 1980s, coinciding with the widespread fluoroquinolone usage. The ST22-PT-eQR subclones emerged in around 2017 and are accumulating resistance genes. Conclusion Vigilance is crucial for eQR high-risk clones, particularly the convergent ST22-PT-eQR subclones that accumulate resistance and virulence traits, posing risks for ear infections. Clinical trial number Not applicable.